1974
DOI: 10.1128/jvi.14.2.333-340.1974
|View full text |Cite
|
Sign up to set email alerts
|

Marine Transducing Bacteriophage Attacking a Luminous Bacterium

Abstract: The isolation and partial characterization of a marine bacteriophage attacking a strain of luminous bacteria is described, including some physical, biological, and genetic properties. It is a DNA phage of density of 1.52 with a long flexible tail and an apparently icosohedral head. With respect to stability in suspension,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
(9 reference statements)
1
18
0
Order By: Relevance
“…Many vibriophages have been described (1,4,(7)(8)(9)(10)(11)(12)16). Most of them are for Vibrio cholerae, some for V. parahaemolyticus, and a few for other Vibrio species.…”
mentioning
confidence: 99%
“…Many vibriophages have been described (1,4,(7)(8)(9)(10)(11)(12)16). Most of them are for Vibrio cholerae, some for V. parahaemolyticus, and a few for other Vibrio species.…”
mentioning
confidence: 99%
“…Some were also shown to be psychrophilic [23] The most convincing transduction studies carried out in environmentally relevant experiments were in situ studies in fresh water where transduction of plasmid DNA was shown in Pseudomonas aeruginosa [24]. To our knowledge, no attempts have been made to study transduction directly in marine waters.…”
Section: Transductionmentioning
confidence: 99%
“…It was almost three decades ago that the first description of bacteriophages infecting luminescent bacteria was reported (Keynan et al, 1974). After a long gap of 25 years, bacteriophage-mediated toxicity of V. harveyi in Penaeus monodon by the transfer of a gene controlling toxin production was reported (Ruangpan et al, 1999), followed by the description of VHML associated with toxin-producing strains (Oakey & Owens, 2000;Oakey et al, 2002).…”
Section: Introductionmentioning
confidence: 99%